The Role of Trichoderma in the Rhizosphere of Tomato Plants - Harcz, Péter (Acta Agraria Debreceniensis, 2003)
It is well established that microorganisms are closely associated with the roots of plants can directly influence plant growth and development. Species of Trichoderma, on the other hand are primarily studied for their ability to control plant disease. The ability of species of Trichoderma to directly promote or inhibit plant growth has been noted for many years.Tomatoes were treated with different Trichoderma strains by seed treatment and soil inoculation. The Trichoderma were grown on malt-agar medium and conidia were washed off by sterile water for making suspension which contained 107 CFU/ml (colony forming unit/ml). The suspension was used for seed treatment and for the soil inoculation by watering as well. The artificial soil inoculation was made by Trichodermas growing on grounded maize were mixed in mould and tomato seed were sown in it. Tomato seeds were also sown in bags made of close-meshed material which allowed the soil microorganisms to colonize the roots but it simultaneously protected the roots from soil contamination. Roots were put on Trichoderma selective medium to check the root colonization of the Trichoderma.The tomato plants were bedded out in a field in four repetition. After harvesting by hand the results supported by statistics shown that there was significant differences between the yield of the untreated and treated tomato plants by Trichoderma strains.